Nonalcoholic fatty liver disease progresses into severe NASH when physiological mechanisms of tissue homeostasis collapse - Sookoian, Silvia Cristina (2018)
Phenotypic modulation of NAFLD-severity by molecules derived from white (adipokines) and brown (batokines) adipose tissue may be important in inducing or protecting against the progression of the disease. Adipose tissue-derived factors can promote the progression of NAFLD towards severe histological stages (NASH-fibrosis and NASHcirrhosis). This effect can be modulated by the release of adipokines or batokines that directly trigger an inflammatory response in the liver tissue or indirectly modulate related phenotypes, such as insulin resistance. Metabolically dysfunctional adipose tissue, which is often infiltrated by macrophages and crown-like histological structures, may also show impaired production of anti-inflammatory cytokines, which may favor NAFLD progression into aggressive phenotypes by preventing its protective effects on the liver tissue.